2020
DOI: 10.3389/fpubh.2020.574968
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Wastewater as a Reservoir for Antibiotic Resistance Genes: A Meta-Analysis

Abstract: Background: The emergence and dissemination of antibiotic resistance genes (ARGs) in the environment poses a huge global health hazard. Hospital wastewater (HWW), in which a high density of antibiotic residues and antibiotic-resistant bacteria are present, may be a reservoir of ARGs dissemination into the environment. Our meta-analysis comprehensively analyzes the prevalence of ARGs in HWW, as well as the influencing factors in ARGs distribution.Methods: Online databases were used to search for literature usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…We note that this activity loss may be beneficial when 1 is used as an antibacterial – this would reduce the risk of resistance development in environmental settings such as hospital wastewater. [33] …”
Section: Resultsmentioning
confidence: 99%
“…We note that this activity loss may be beneficial when 1 is used as an antibacterial – this would reduce the risk of resistance development in environmental settings such as hospital wastewater. [33] …”
Section: Resultsmentioning
confidence: 99%
“…This is partly due to the use, overuse, and misuse of antibiotics by healthcare professionals and patients, but also in animal husbandry and agriculture [2][3][4][5][6]. Antibiotic resistant bacteria (ARB) can be introduced into the environment by different routes [7], including wastewater from the general human population [8][9][10][11][12][13][14][15]. These residual waters arrive and are collected at municipal wastewater treatment plants (WWTPs).…”
Section: Introductionmentioning
confidence: 99%
“…Hospital wastewater is believed to contain more pharmaceutically active compounds than municipal wastewater, as well as the excrement of hospitalized patients who are more likely to harbor bacteria rich in ARGs. Indeed, a previous study showed hospital wastewater presenting more types and higher abundance of ARGs than those in most wastewater systems ( Zhang et al, 2020 ). However, using metagenomics which enables more comprehensive profiling of the resistomes, we found opposite trends in this study ( Figures 1 , 3 ).…”
Section: Discussionmentioning
confidence: 98%